Pore network modeling of catalyst deactivation by coking, from single site to particle, during propane dehydrogenation. Issue 1 (15th October 2018) - Ye, Guanghua; Wang, Haizhi; Duan, Xuezhi; Sui, Zhijun; Zhou, Xinggui; Coppens, Marc‐Olivier; Yuan, Weikang
Abstract : A versatile pore network model is used to study deactivation by coking in a single catalyst particle. This approach allows to gain detailed insights into the progression of deactivation from active site, to pore, and to particle—providing valuable information for catalyst design. The model is applied to investigate deactivation by coking during propane dehydrogenation in a Pt‐Sn/Al2 O3 catalyst particle. We find that the deactivation process can be separated into two stages when there exist severe diffusion limitation and pore blockage, and the toxicity of coke formed in the later stage is much stronger than of coke formed in the early stage. The reaction temperature and composition change the coking rate and apparent reaction rate, informed by the kinetics, but, remarkably, they do not change the capacity for a catalyst particle to accommodate coke. Conversely, the pore network structure significantly affects the capacity to contain coke. © 2018 The Authors. AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers. AIChE J, 65: 140–150, 2019